The Pattern of Informal Education in Extra-Campus Student Organization - Bangun Setiyawan Nugroho (Pascasarjana UM, 2014)
Pola Pendidikan Informal dalam Organisasi Mahasiswa Ekstra UniversiterAbstract: This study aims to determine the underlying causes of informal education in the Student Organizations Extra university (OMEU) successfully reproduces many Indonesian leaders and what patterns of informal education in the association OMEU. The research approach used is qualitative case study research tradition, in this case the researchers used a multi-case. Sources of data in this study primarily obtained from informants who are leaders HMI, GMNI, and PMII in Malang. Data collection techniques used were interviewed, observation and documentation. The analysis technique used is the data management; reading and making notes; describe, classify, and interpretation; and present and visualize. The results of this study that (1) informal education in OMEU produce many leaders of Indonesia, (2) pattern of informal education in OMEU an interaction that occurs continu-ously between individuals, communities, and the environment.Key Words: patterns of informal education, extra student organizations university Abstrak: Penelitian ini bertujuan untuk mengetahui sebab-sebab yang mendasari pendidikan informal dalam Organisasi Mahasiswa Ekstra Universiter (OMEU) berhasil mereproduksi banyak pemimpin bangsa Indonesia dan seperti apa pola pendidikan informal dalam pergaulan OMEU. Pendekatan pe-nelitian yang digunakan adalah kualitatif dengan tradisi penelitian studi kasus, peneliti menggunakan multi kasus. Sumber data dalam penelitian ini diperoleh dari para informan yang merupakan tokoh HMI, GMNI, dan PMII di Kota Malang. Teknik pengumpulan data yang digunakan adalah wawancara, observasi dan dokumentasi. Teknik analisis yang digunakan adalah pengelolaan data; membaca dan membuat catatan; mendiskripsikan, mengklasifikasi, dan menginterpretasi; serta menyajikan dan memvisualisasikan. Hasil penelitian ini bahwa (1) pendidikan informal di OMEU menghasilkan banyak pemimpin bangsa Indonesia, (2) Pola pendidikan informal di OMEU merupakan interaksi yang terjadi secara terus menerus antara individu-individu, komunitas, dan lingkungan.Kata kunci: pola pendidikan informal, organisasi mahasiswa ekstra universiter